Amplifying Street Knowledge through Practice-as-Research: Sound System Outernational #5 in Naples, Italy - D’Aquino, Brian; Pârvan, Oana (Journal of World Popular Music, 2021)
Based on a first-hand account of the SSO#5 event, the authors discuss the challenges of grounding the organization of an international academic event in the local environment of Naples, a Southern Italy city with a strong sound system tradition. An ethnographic account of the Italian and Naples scene, including interviews with local sound system pioneers, will provide the context. The overarching intention animating the planning of the event was to acknowledge the way academic research can interact with local and global grassroots music movements in a transformative way, establishing connections, nurturing skills and promoting mutual recognition. More specifically, the event was aimed at amplifying the value of the already-existing scene, turning up the self-confidence of its practitioners and boosting the acknowledgement of sound system practice as an academic research field. This was achieved through the active involvement of local practitioners and activists in the conception of the event, to achieve the mutual trust and respect between participants from different backgrounds, which made the event itself a form of practice-as-research in terms of adding to an ongoing learning process.